Dampak Indomaret Dan Alfamart Terhadap Pedagang Eceran di Jalan Cipta Karya Kelurahan Tuah Karya Tampan Pekanbaru - Waldelmi, Idel (Jurnal Daya Saing, 2017)
Retailing is a kind of business that can economically suffice people needs and provide business profit for some business players. The development of Pekanbaru city goes along with modern retail business growth, spesifically in Jalan Cipta Karya, Kelurahan Tuah Karya, Kecamatan Tampan.. This study uses descriptive method which is focusing on actual phenomenon and describing studied object as well as interpreting it rationally and accurately. Study reveals the decrease of income as the consequence of Indomaret and Alfamart exixtence for the amount of 42,24%. This decrease caused by 2 of 4 factors i.e price and service, meanwhile location and product variation shows no significant effect. Price shows negative effect, which means, higher price implemented by Indomaret and Alfamart causes increase the retailer’s income. Service shows positive effect, which means, the better service of Indomaret and Alfamart will increase the income Keywords: Indomaret dan Alfamart, Retailer and Income